Genetic testing for Lynch syndrome in the province of Ontario. Issue 11 (28th March 2016) - Wang, Marina; Aldubayan, Saud; Connor, Ashton A.; Wong, Beatrix; Mcnamara, Kate; Khan, Tahsin; Semotiuk, Kara; Khalouei, Sam; Holter, Spring; Aronson, Melyssa; Cohen, Zane; Gallinger, Steve; et al.
Abstract : BACKGROUND: In November 2001, genetic testing for Lynch syndrome (LS) was introduced by the Ministry of Health and Long‐Term Care (MOH) in Ontario for individuals at high risk for LS cancers according to either tumor immunohistochemistry staining or their family history. This article describes the outcomes of the program and makes recommendations for improving it and informing other public health care programs. METHODS: Subjects were referred for molecular testing of the mismatch repair (MMR) genes MutL homolog 1, MutS homolog 2, and MutS homolog 6 if they met 1 of 7 MOH criteria. Testing was conducted from January 2001 to March 2015 at the Molecular Diagnostic Laboratory of Mount Sinai Hospital in Toronto. RESULTS: A total of 1452 subjects were tested. Of the 662 subjects referred for testing because their tumor was immunodeficient for 1 or more of the MMR genes, 251 (37.9%) carried a germline mutation. In addition, 597 subjects were tested for a known family mutation, and 298 (49.9%) were positive; 189 of these 298 subjects (63.4%) were affected with cancer at the time of testing. An additional 193 subjects were referred because of a family history of LS, and 34 of these (17.6%) had a mutation identified. CONCLUSIONS: These results indicate that the provincial criteria are useful in identifying LS carriers after an MMR‐deficient tumor is identified. Placing greater emphasis on testing unaffected relatives in families with a known mutation may identify more unaffected carriers and facilitate primary prevention in those individuals. Cancer 2016;122:1672‐9 . © 2016 American Cancer Society . Abstract : The province of Ontario, Canada, sponsors a genetic testing program that is effective in identifying Lynch syndrome mutation carriers. Through the testing of more unaffected family members, more cancers may be prevented.